Foraging behavior of tyrant flycatchers (Aves, Tyrannidae) in Brazil - Gabriel, V. D.; Pizo, M. A. (Soc Brasileira Zoologia, Univ Federal Parana, 2005)
In this paper we present data on the foraging maneuvers and substrates used to capture preys by 28 species of tyrant flycatchers (Tyrannidae) in Brazil. For six species: Arundinicola leucocephala Linnaeus, 1764, Fluvicola nengeta Linnaeus, 1766, Machetornis rixosa Vieillot, 1819, Myiozetetes similis Spix, 1825, Pitangus sulphuratus Linnaeus, 1766, and Tyrannus melancholicus Vieillot, 1819 -, we go further to investigate perch height, search time, sally distance, and sally angle. With a few exceptions, sally strike was the most frequent foraging maneuver. Living foliage and air were the most frequent substrates used to capture preys. Among the six species Studied in detail we found three distinct groups of perch heights: F. nengeta and M. rixoso foraged on the ground, A. leucocephala with A sulphuratus were medium-height foragers, and T. melancholicus and H. similis form the third group for which prey attacks usually start from perches from the ground up to 3 m. With the exception of A sulphuratus, which had the longest search time, the other five species did not differ in this aspect of the foraging behavior. Three groups were also discernible in relation to sally distance: F. nengeta and M. rixosa usually attacked prey close (< 2 m) to them, A leucocephala, A sulphuratus and M. similis form a medium-distance (3-4 m) group, and T. melancholicus had the longest sally distances (up to 12 m). Birds differ in details of the sally angle that, together with other subtle differences in the foraging behavior, may render important differences in prey selection.
Keywords: birds; feeding behavior; foraging maneuvers; prey selection